1988
DOI: 10.2134/jeq1988.00472425001700020004x
|View full text |Cite
|
Sign up to set email alerts
|

Minesoil Property Effects on the Height of Ten‐Year‐Old White Pine

Abstract: Thirty‐four 10‐yr‐old white pines (Pinus strobus L.) growing on reclaimed minesoils in Virginia were selected to evaluate the effects of selected minesoil properties on tree growth. A 1‐m deep backhoe pit was dug at the base of each tree to determine rooting depth, and surface soil samples (0–10 cm) were collected for analysis of selected physical and chemical properties. Multiple regression analysis was used to model the combined effects of minesoil properties on tree height. The minesoil variable that had th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
1

Year Published

1994
1994
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 0 publications
3
54
1
Order By: Relevance
“…However, given the renewed interest in reforesting mined sites with native hardwoods, we are trying to understand species-specific site limitations and reclamation requirements in order to prescribe reclamation procedures that will allow their use and successful establishment. Our early studies of mine soil effects on the growth of pines (Torbert et al, 1988;Andrews et al, 1998), and our more recent studies on mine soil quality effects on hardwoods (Rodrigue and Burger, 2002a;Rodrigue and Burger, 2002b), show that forest site quality is primarily a function of soil parent material, degree of mine soil compaction, and slope aspect. Given that a selected overburden invariably becomes a substitute for native topsoil on reclaimed sites, its physics, chemistry and biology will largely determine the success of planted trees.…”
Section: Introductionmentioning
confidence: 80%
“…However, given the renewed interest in reforesting mined sites with native hardwoods, we are trying to understand species-specific site limitations and reclamation requirements in order to prescribe reclamation procedures that will allow their use and successful establishment. Our early studies of mine soil effects on the growth of pines (Torbert et al, 1988;Andrews et al, 1998), and our more recent studies on mine soil quality effects on hardwoods (Rodrigue and Burger, 2002a;Rodrigue and Burger, 2002b), show that forest site quality is primarily a function of soil parent material, degree of mine soil compaction, and slope aspect. Given that a selected overburden invariably becomes a substitute for native topsoil on reclaimed sites, its physics, chemistry and biology will largely determine the success of planted trees.…”
Section: Introductionmentioning
confidence: 80%
“…McFee et al (1981) listed soluble salts as one of the most influential soil properties on Indiana mine soils, especially when levels exceeded 1300 mg kg -1 . Torbert et al (1988) also suggested that levels above 1000 mg kg -1 could affect tree survival and growth. According to the Soil and Plant Analysis Council (1992), 1000 mg kg -1 is considered "moderately saline," where seedlings may be injured and yields of salt-sensitive crops are restricted.…”
Section: Resultsmentioning
confidence: 99%
“…The effects of mine soil selection (Torbert et al, 1988), mine soil compaction (Torbert and Burger, 1996), and tree-compatible ground cover on tree survival and growth were studied and documented. Research findings were used to develop preliminary regional reclamation guidelines for reforestation (Burger and Zipper, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Different reclamation approaches can result in a wide range afforest site productivity. Across 36 reclaimed sites in Virginia, all of which had 10-year-old white pines, Torbert et al (1988a) found site index (a measure of forest site quality based on predicted heights of trees at age 50) ranging from 35 to 110 ft. Assuming these stands are harvested at age 35, a white pine stand growing on an area with a site index of 110 will yield over 10 times the volume of wood as a stand growing on an area with a site index of 35.…”
Section: Importance Of Productive Mine Soils For Forestsmentioning
confidence: 99%